Financial Behaviour Outsourced Workers in Batam City: Analysis Of Financial Technology and Social Influence - Etty Sri Wahyuni; Rozaini Rosli (International Forum of Researchers and Lecturers, 2024)
The purpose of this research is to know and analyze the influence of financial technology and social influence partially and simultaneously on financial behavior of outsourced workers in Batam City. The method used in this research uses a method, namely the type of research used in this research is a quantitative research method. This research uses an analytical tool is SPSS Version 23. The population in this study was all students at Stambuk Potensi Utama University in 2023 totaling 1253 students. The population in this study are all outsourced workers scattered in Batam City whose numbers cannot be known and recorded with certainty. The sampling method in this study uses accidental sampling technique. By using the Zikmund formula, the final sample size used was 100 people. The results of this research are (1) Financial technology partially has a positive and significant effect on financial behaviour, (2) Social influence partially has a positive and significant effect on financial behaviour (3) Financial technology and social influence together or simultaneously have a positive effect and significant to the financial behavior of outsourced workers in Batam City.